Kamera i poeta doctus? O filmach Edwarda Żebrowskiego z perspektywy lotu ptaka - Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Camera and poeta doctus? About Edward Żebrowski’s Films This text conserns the excelent polish director Edwrad Żebrowski’ creation. It has character of synthetic discussion. It shows main formal questions of it this creation and main problems of it. It is considered also the question of anachronism of these movies.